Student loans repayment and recovery: a case study of Yayasan Sabah Group / Mohammad Rasidin Abu Sari - Abu Sari, Mohammad Rasidin (Faculty of Business and Management, 2009)
This study is to determine the level of financial performance focus on student loans repayment and recovery. The purpose of this study to researcher is to know the performance of student loans summary by focusing on their loan repayment summary for the past few years, starting in the year 2003 until 2007. Besides that, this study shows us how the process of repayment loan especially on student loans. The paper is structured as follows. The following, introduction section in Chapter 1, introduces the background of company and followed by Chapter 2, which is the literature review. In Chapter 3, researcher focused on the research methodology applied in the research. While a brief findings and analyze of data sources and main findings on repayment and recovery ratios are presented in Chapter 4. Conclusions and any recommendations for these issues follow in the final section which is in Chapter 5.